Analysis Of The Influence Of K-Drama Culture On Consumer Perpection And Business Communication Strategies Og Korean Street Food Business Actors In Cidu Market, Makassar City - Wisudawaty, Ika; Wulan Purnamasari (Cita konsultindo, 2024)
This study examines the influence of K-Drama culture on consumer perception and business communication strategies of Korean Street Food business actors in Cidu Market, Makassar. Using a quantitative approach with a cross-sectional survey design, data was collected from 150 respondents consisting of consumers and business actors. The results of the analysis show that most of the respondents are exposed to K-Drama and have a high interest in Korean street food. The use of elements of Korean culture in marketing strategies has been shown to increase buying interest and consumer confidence. Regression analysis indicates that exposure to K-Drama has a significant positive influence on consumer perception and business communication strategies, with regression coefficients of 0.7 and 0.6, respectively. The findings underscore the importance of elements of Korea's pop culture in shaping consumer behavior and advise businesses to integrate more elements of Korean culture in their business strategies to attract consumers.